Paleontological study of the echinoderms in the qom formation (central iran) (2007)
The Qom formation was formed in the Oligo-Miocene during the final sea transgression in Central Iran (Figure 1). The best outcrop is located in the vicinities of the Qom City, approximately 130km at the south of Tehran. In general, the great heights of the zone are the result of intense tectonic activities. These heights have a number of faults and folds. Echinoderms are one of the most important and numerous fossil groups present in the Qom Formation and confirm the relationship of this environment with free waters. In the present investigation more than 100 prepared samples werestudied and 17 species were identified, scanned and classified. These fossils are more abundant in the upper part of the A member, which illustrates the abundance and diversity in C1 and C3 sub-membersbelonging to the C member. To classify these samples, classical and up-to-date methods were used.However, the systematic schemes were used more frequently (Moore, 1966; 1969-1971). Besides these studies, the other concomitant microfossils in the formation were investigated simultaneously to estimate the accurate age of them. It is concluded that the study of Oligo-Miocene Echinoderms present in the Qom formation is essential and important because, at the same time, the Central Iran Sea had a communicative role between the Indo-Pacific Ocean and the  Mediterranean Sea.